Penerapan Metode SAW dan TOPSIS dalam Sistem Rekomendasi Lowongan Kerja Bali (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2022)
Job information is important for humans, because almost every human being needs a job. The more unemployed human resources in an area, the higher the demand for job vacancies. Bali is one of the areas that has increased unemployment since the pandemic, Bali has a workforce of 2.6 million who need work. To help Bali job seekers find jobs that match their criteria. In this study, a Bali job vacancy recommendation system was built based on the preferences of respondents residing in Bali. This system will apply the SAW-TOPSIS method in providing recommendations. For the development method, the Waterfall Model will be used. Job vacancies data will be collected on a secondary basis via the internet. The criteria and weighting in the recommendations are based on the results of the respondent's survey. The results of this study note that the application of the SAW-TOPSIS method in the Bali job vacancy recommendation system is in accordance with manual calculations and for direct testing to users using usability testing with 20 respondents the results are 83.39% which shows the system has a very good usability value.